Transcription Factor CitERF16 Is Involved in Citrus Fruit Sucrose Accumulation by Activating CitSWEET11d - Hu, Xiaobo; Li, Shaojia; Lin, Xiahui; Fang, Heting; Shi, Yanna; Grierson, Donald; Chen, Kunsong (Frontiers in Plant Science, 2021)
Sugars are the primary products of photosynthesis and play an important role in plant growth and development. They contribute to sweetness and flavor of fleshy fruits and are pivotal to fruit quality, and their translocation and allocation is mainly dependent on sugar transporters. Genome-wide characterization of Satsuma mandarin identified eighteen SWEET family members that encode transporters which facilitate diffusion of sugar across cell membranes. Analysis of the expression profiles in tissues of mandarin fruit at different developmental stages showed that CitSWEET11d transcripts were significantly correlated with sucrose accumulation. Further studies indicated that overexpression of CitSWEET11d in citrus callus and tomato fruit showed a higher sucrose level compared to wild-type, suggesting that CitSWEET11d could enhance sucrose accumulation. In addition, we identified an ERF transcription factor CitERF16 by yeast one-hybrid screening assay which could directly bind to the DRE cis-element on the promoter of CitSWEET11d. Overexpression of CitERF16 in citrus callus significantly induced CitSWEET11d expression and elevated sucrose content, suggesting that CitERF16 acts as a positive regulator to promote sucrose accumulation via trans-activation of CitSWEET11d expression.